Analisis Kesiapan Pelaku Usaha Rumah Potong Unggas Di Kecamatan Tanah Merah Kabupaten Bangkalan Terhadap Sertifikasi Halal - Fauzan; Nashrullah, M. Faiz (Journal of Islamic Economic and Law (JIEL), 2024)
Halal certification has a very important role in the food industry, especially in Indonesia, where the majority of the population is Muslim. Based on the enactment of the Halal Product Guarantee Law (Law No. 33 of 2014), all food business actors are required to obtain halal certification to provide certainty to consumers that the products consumed are free from non-halal ingredients and processes. This research focuses on the importance of halal certification for poultry slaughterhouse business actors. The method used is qualitative with a descriptive approach to describe the understanding and implementation of halal certification in poultry slaughterhouses. The research subjects were poultry slaughterhouse business operators in Tanah Merah District, Bangkalan Regency. Data was obtained through in-depth interviews and documentation studies to obtain precise information regarding the phenomena studied. Primary data was obtained directly from business actors, while secondary data was collected from literature and other relevant sources. The research results show that there are differences in understanding and response to halal certification obligations between small and medium scale poultry slaughterhouse business actors. Large poultry slaughterhouse businesses tend to be more prepared to comply with this obligation, seeing it as an important step to maintain product quality and increase consumer confidence. Meanwhile, small poultry slaughterhouse businesses feel that certification costs are an additional burden that will affect the price of their products.